Implementasi Prinsip Bagi Hasil dan Resiko di Perbankan Syariah (Studi di Bank Aceh Syariah Cabang Meulaboh Aceh Barat) - Rizuwan, Malik (Tadabbur: Jurnal Peradaban Islam, 2019)
This research entitled Implementation of Profit Sharing and Risk in Sharia Banking (Study at Bank Aceh Syariah Branch Meulaboh West Aceh), with the aim of: First, to know the implementation of aqad funding products at Bank Aceh Syari'ah Branch Meulaboh. Second, to know the implementation of financing product aqad at Bank Aceh Syari'ah Branch Meulaboh and Third, to know the obstacle in implementation of profit sharing principle and risk at Bank Aceh Syari'ah Branch Meulaboh. The method used in this study is a qualitative method with data collection techniques such as observation, interview and documentation. While the results of this study indicate that: First, the implementation of aqad funding products at Bank Aceh Syariah Branch Meulaboh done using wadi'ah and Mudharabah principles. Wadi'ah principle with aqad wadi'ah giro product and wadi'ah savings. While the principle of mudharabah using mudharabah savings account and mudharabah deposit. In the calculation of profit sharing only on the principle of mudharabah while in principle wadi'ah only a bonus given to the willingness of the bank. The calculation pattern for the results is by using the revenue sharing principle which means the calculation of the total revenue from the management of funds and the amount of the share of profit sharing depends on the initial agreement. Second, the implementation of aqad of financing products at Bank Aceh Syariah Branch Meulaboh using several contracts such as purchase and purchase agreement, profit sharing contract, lease agreement, contract and guarantee credentials trust. The profit-sharing agreement uses mudaraba and musharaka. In the implementation of financing with this principle is still low compared with other financing principles such as murabaha, this is due to several factors such as the difficulty of finding and obtaining honest customers, good character and high integrity, high risk to be borne by banks, the attitude of people who still consider banking products sharia is the same as conventional banks and the absence of moral standards in financing activities for the results. Third. obstacles in the implementation of profit sharing principles and risks at Bank Aceh Syari'ah Branch Meulaboh such as Human Resources, Sharia Banking Management, Limited Office Network, and still weak government regulations on Sharia Banking.